y-3.8y-6=-1.9y-11.4

Simple and best practice solution for y-3.8y-6=-1.9y-11.4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y-3.8y-6=-1.9y-11.4 equation:


Simplifying
y + -3.8y + -6 = -1.9y + -11.4

Reorder the terms:
-6 + y + -3.8y = -1.9y + -11.4

Combine like terms: y + -3.8y = -2.8y
-6 + -2.8y = -1.9y + -11.4

Reorder the terms:
-6 + -2.8y = -11.4 + -1.9y

Solving
-6 + -2.8y = -11.4 + -1.9y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '1.9y' to each side of the equation.
-6 + -2.8y + 1.9y = -11.4 + -1.9y + 1.9y

Combine like terms: -2.8y + 1.9y = -0.9y
-6 + -0.9y = -11.4 + -1.9y + 1.9y

Combine like terms: -1.9y + 1.9y = 0.0
-6 + -0.9y = -11.4 + 0.0
-6 + -0.9y = -11.4

Add '6' to each side of the equation.
-6 + 6 + -0.9y = -11.4 + 6

Combine like terms: -6 + 6 = 0
0 + -0.9y = -11.4 + 6
-0.9y = -11.4 + 6

Combine like terms: -11.4 + 6 = -5.4
-0.9y = -5.4

Divide each side by '-0.9'.
y = 6

Simplifying
y = 6

See similar equations:

| 12x^2=77 | | (7-v)(4v-2)=0 | | 3(c+2)+1=5c-1 | | x^2+x=1.52 | | 509.8104=2*3.14*r^2+2*3.14*r*55.6 | | -7(-5k-7)=84 | | 5(k-3)=(k-5) | | (7x-15)1/3 | | 6(5/9) | | F(x)=(-6)+3 | | -1+20n+15=8n-10+6 | | 70-a=25 | | .05x+09(28000-x)=2400 | | -2+b=3 | | 52x=1/625x | | q=50-2p | | -1+20n+3=8n-10+6 | | 2y+3x+1=0 | | 9=-r | | 12x^2-6x=45 | | b+8b+1=19 | | 0=16t^2-40t-25 | | 100=(65000)x(1+0.016)100 | | r+r+8=14 | | -4(3(-5)-5)= | | F(x)=(x+5)-6 | | -4+35y-1=21y+18+5 | | (21y^5-5y^4-18y^3)/(3y^4) | | 3x-4x+5x-9x= | | f(x)=x^2-16x+67 | | r+r+8=6 | | =(65000)x(1+0.016)100 |

Equations solver categories